Rancang Bangun E-Magazine Dengan Menggunakan Metode Rapid Application Development (RAD) Di SMK Bina Putra Mandiri Parung Panjang - Imannudin; Ari Syaripudin (CV. Shofanah Media Berkah, 2023)
Dissemination of information at Bina Putra Mandiri Vocational School still uses conventional methods and seems monotonous by way of direct announcements to each class, school field or posting paper flyers on bulletin boards. Information about various activities in schools is often not known by teachers or students, this happens because it is less communicative and does not interest listeners or readers. In order for information dissemination activities to run effectively and efficiently, a computerized e-magazine system is needed to integrate school activity data in one integrated database, so that the dissemination of information becomes more informative, communicative, recreational and interactive. The method used in designing the system is the Rapid Application Development (RAD) method and presenting the data using Unified Modeling Language (UML) tools, including Use Case diagrams, Activity diagrams, Sequence diagrams and Class diagrams. The results of this study E-Magazine can help facilitate students or teachers in obtaining information or activities at Bina Putra Mandiri Vocational School, with the e-magazine information system that has been built, the dissemination of information becomes more informative, communicative, recreational and interactive, this evidenced by the results of the attached user interviews.